2012
DOI: 10.5194/angeo-30-1693-2012
|View full text |Cite
|
Sign up to set email alerts
|

Spatial characteristics of wave-like structures in diffuse aurora obtained using optical observations

Abstract: Abstract. We present the results of a statistical study using optical images from ALIS (Auroral Large Imaging System) to investigate the spatial and temporal variations of structures in diffuse aurora. Analysis of conjugate Reimei data shows that such fine structures are a result of modulation of highenergy precipitating electrons. Pitch angle diffusion into the loss cone due to interaction of whistler mode waves with plasma sheet electrons is the most feasible mechanism leading to high-energy electron precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…These aurorae have been shown to be associated with electrons ≥ 8 keV scattered into the loss-cone from trapped magnetospheric particles . A statistical analysis of about 500 diffuse stripelike structures recorded during 5 events have found the scale sizes of these stripes to be on average about 13-14 km, and with a separation of about 5-23 km between each other (Axelsson et al, 2012). This separation maps to about 75-345 km in the equatorial plane of the magnetosphere.…”
Section: Morphology Of Non-pulsating Diffuse Aurora Small-scale Strumentioning
confidence: 98%
See 2 more Smart Citations
“…These aurorae have been shown to be associated with electrons ≥ 8 keV scattered into the loss-cone from trapped magnetospheric particles . A statistical analysis of about 500 diffuse stripelike structures recorded during 5 events have found the scale sizes of these stripes to be on average about 13-14 km, and with a separation of about 5-23 km between each other (Axelsson et al, 2012). This separation maps to about 75-345 km in the equatorial plane of the magnetosphere.…”
Section: Morphology Of Non-pulsating Diffuse Aurora Small-scale Strumentioning
confidence: 98%
“…This separation maps to about 75-345 km in the equatorial plane of the magnetosphere. Using ionospheric equivalent current estimates from ground magnetometers, Axelsson et al (2012) concluded that the stripes move equatorward at a speed close to zero in the plasma convection frame (~100-200 m/s). As in the case of the dayside aurora, the fine structures are understood to be a visual manifestation of cold plasma density or magnetic field structures in the equatorial magnetosphere (Axelsson et al, 2012;Ebihara et al, 2010).…”
Section: Morphology Of Non-pulsating Diffuse Aurora Small-scale Strumentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we call these key local structures (KLS). Extracting the concerned KLS can not only help classify the auroral images but also provide the position information to statistically analyze both spatial and morphological evolution of aurora (Axelsson et al, ; Niu et al, ).…”
Section: Introductionmentioning
confidence: 99%